“Til Asylernes Venner og Veninder”: Kommenteret tekstudgivelse om Grundtvigs kamp for asylskolernes frihed - Overgaard, Ulrik (Grundtvig-Studier, 2006)
“Til Asylernes Venner og Veninder Kommenteret tekstudgivelse om Grundtvigs kamp for asylskolernes frihed [Grundtvig ’s fight for freedom of the charity schools] Transcription by Ulrik Overgaard In May 1829 the Danish crown princess Caroline Amalie founded a sanctuary for orphans in Copenhagen. Grundtvig was a personal friend of the princess and from 1838 he usually gave a speech at the children’s annual Christmas party. On 19 September 1841, Caroline Amalie also took the initiative to establish a school, Dronningens Asylskole, which was connected to the sanctuary. Grundtvig became the director and P. O. Boisen the head of this school. The teachers were all grundtvigians and the grundtvigian ideas of a liberal alternative to the public Danish primary school were realized here, thus making Dronningens Asylskole the first of the so-called Danish friskoler (liberal schools). This article, hitherto unprinted, is an example of Grundtvig’s keen interest in the welfare of the sanctuaries in Copenhagen. It is printed here to emphasize Grundtvig’s commitment to the Danish primary school system in general, which scholarship has often neglected in favour of his interest in the folkhighschools. No major research has therefore been undertaken on this topic since K. E. Bugge’s dissertation Skolen for Livet from 1965, which was unquestionably a milestone in the research of Grundtvig’s educational ideas even though it dealt mostly with adult education.